Switched Mode Power Supplies Comparison: PI, Cascade PI and Poiscast Controller - Augustine Egwebe (2021 International Conference on Electrical, Computer and Energy Technologies (ICECET), 2022)
Renewable energy is gradually becoming the most promising type of power generation that could replace fossil fuels in the future. Solar or photovoltaic (PV) based energy is one of the most widely used forms of renewable energy is. For the efficient performance of PV systems, Switched Mode Power Supplies (SMPS) must be designed appropriately to boost voltage output from the PV system in especially during periods of low solar irradiance. The application of SMPS has been increasing recently due to their efficiency. The primary consideration in the use of these systems is to control their dynamics and performance since they possess non-linearity. This necessitates the implementation of a robust controller in the system. This paper presents an averaged model of a boost converter (DC-DC SMPS) working in continuous conduction mode (CCM), and its performance is analysed under three different control techniques. These controllers are Single PI, Cascade PI, and Hybrid Controller (PI and Posicast). The results obtained from this study showed that the single PI control produced more significant oscillations at a steady-statecompared with Cascade PI and the Hybrid Controller. However, the Single PI controller also had longer rise times compared to the other control schemes. The Hybrid controller had reduced oscillations at a steady-state compared to the Cascade PI control. It is, therefore, it-is recommended that a Hybrid controller design SMPS systems offers improved performance and efficiency for renewable energy systems.